Species responses to weather anomalies depend on local adaptation and range position - Yolanda Melero; Luke C. Evans; Mikko Kuussaari; Reto Schmucki; Constantí Stefanescu; David B. Roy; Tom H. Oliver (Communications Biology)
Abstract Species show intra-specific variation in responses to climate change linked to adaptation to the local climatic conditions. Likewise, species are expected to be more resilient to climate change at the centre of their bioclimatic niche, but this pattern is not general. We show that species sensitivity to climatic anomalies varies with local adaptation and the position in the bioclimatic niche, using long-term butterfly monitoring data for 34 species. Climatic anomalies negatively affected all populations of locally adapted species. Globally adapted species were positively or negatively affected by climatic anomalies, depending on population location and direction of anomalies. These responses impacted population trends as globally adapted species showed steeper declines at the trailing margin. Surprisingly, locally adapted species showed stable abundances at the trailing margin, but declines at the leading; which could be explained by the with the 'warmer is better' hypothesis where thermodynamics limit insect performance at cooler conditions.